2021
DOI: 10.3389/fpls.2021.686121
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Fragmented Self-DNA Is Involved in Plant Responses to Biotic Stress

Abstract: A growing body of evidence indicates that extracellular fragmented self-DNA (eDNA), by acting as a signaling molecule, triggers inhibitory effects on conspecific plants and functions as a damage-associated molecular pattern (DAMP). To evaluate early and late events in DAMP-dependent responses to eDNA, we extracted, fragmented, and applied the tomato (Solanum lycopersicum) eDNA to tomato leaves. Non-sonicated, intact self-DNA (intact DNA) was used as control. Early event analyses included the evaluation of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 96 publications
4
28
0
Order By: Relevance
“…Contrastingly, an up-regulation of MPK3 and OXI1 genes resulted from treatments with broccoli, citrus, bean, and maize eDNA. Similarly, CML37 levels of expression were upregulated in A. thaliana plants treated with broccoli and bean eDNA only [60]. In this case, the non-self eDNA had neither pathogenic nor microbial origin to support the hypothesis of the eDNA effect as MAMP/PAMP but these results do support the phylogenetically closeness-related effect described earlier [46,52].…”
Section: Self-edna As a Dampsupporting
confidence: 65%
See 2 more Smart Citations
“…Contrastingly, an up-regulation of MPK3 and OXI1 genes resulted from treatments with broccoli, citrus, bean, and maize eDNA. Similarly, CML37 levels of expression were upregulated in A. thaliana plants treated with broccoli and bean eDNA only [60]. In this case, the non-self eDNA had neither pathogenic nor microbial origin to support the hypothesis of the eDNA effect as MAMP/PAMP but these results do support the phylogenetically closeness-related effect described earlier [46,52].…”
Section: Self-edna As a Dampsupporting
confidence: 65%
“…As reported before [47,60], the plant immune system responds to the detection of both self and non-self eDNA. Due to the effect on plant metabolism seems to be different between eDNA sources, these results suggest a role of eDNA different from the suspected DAMP or MAMP (PAMP) role as a biological plant biostimulant (considering a hormetic effect), activating several metabolic pathways related to both defence and growth processes depending on the dose and the opportunity of applications during plant phenology.…”
Section: Perspectivesmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, fragmented self-exDNA induces intracellular calcium signalling and plasma membrane depolarization [ 87 ], H 2 O 2 production, and MAPK activation [ 55 ] in plants. Recently, it has been shown that after treatment with self-exDNA, tomato leaves activate a typical response to biotic stress characterized by an early response consisting of the plasma membrane depolarization, the increase of intracellular concentration of Ca 2+ and K + ions, and ROS production, accompanied by the modulation of genes involved in plant late responses to biotic stress [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high-temperature stress also activates mitogen-activated protein kinases (MAPKs) and regulates the expression of HSP genes. This may be closely related not only to changes in membrane fluidity but also to calcium signaling induced by high-temperature stress, which is especially required for HSP gene expression and high-temperature stress tolerance acquisition [ 79 , 80 ]. The common features between signals of low- and high-temperature stress are not limited to membrane fluidity changes, calcium signaling and MAPK activation, as they also include ROS, NO, and phospholipid signaling [ 81 , 82 ].…”
Section: Molecular Mechanisms Of Crosstalk Between Ca 2+ ...mentioning
confidence: 99%